Oral Vaccination of Fish – Antigen Preparations, Uptake, and Immune Induction - Mutoloki, Stephen; Munang’andu, Hetron Mweemba; Evensen, Øystein (Frontiers in Immunology, 2015)
The oral route offers the most attractive approach of immunization of fish for a number of reasons: the ease of administration of antigens, it is less stressful than parenteral delivery and in principle, it is applicable to small and large sized fish; it also provides a procedure for oral boosting during grow-out periods in cages or ponds. There are however not many commercial vaccines available at the moment due to lack of efficacy and challenges associated with production of large quantities of antigens. These are required to stimulate an effective immune response locally and systemically, and need to be protected against degradation before they reach the sites where immune induction occurs. The hostile stomach environment is believed to be particularly important with regard to degradation of antigens in certain species. There is also a poor understanding about the requirements for proper immune induction following oral administration on one side, and the potential for induction of tolerance on the other. To what extent primary immunization via the oral route will elicit both local and systemic responses is not understood in detail. Furthermore, to what extent parenteral delivery will protect mucosal/gut surfaces and vice-versa is also not fully understood. We review the work that has been done on the subject and discuss it in light of recent advances that include mass production of antigens including the use of plant systems. Different encapsulation techniques that have been developed in the quest to protect antigens against digestive degradation, as well as to target them for appropriate immune induction are also highlighted.